Penerapan Sistem Deteksi Api dan Gas pada Proyek Ekspansi Lapangan Utara (NFXP) - Zul Fazri Sabily Muttaqin; Purbawati Purbawati; Mad Yusup; Ida Rosanti (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
The research with the title Application of Fire and Gas Detection Systems takes place at the North Field Expansion Project (NFXP). The methods used are direct observation, interviews, simulations and literature studies. The objectives of the study were to determine the application of fire and gas detection systems, and to determine the challenges in the application of fire and gas detection systems in the North Field Expansion Project (NFXP). The results obtained show that the Fire and Gas Detection System implemented at NFXP is in compliance with international safety standards, and the system is able to detect fire threats and gas leaks with high efficiency through advanced detector technology, automatic response, and integration with other safety systems such as IPS and HVAC. The effectiveness of the system is reflected in the ability to detect threats in less than 5 seconds, with detection coverage that meets the target of 90% by one detector and 85% by two or more detectors. The main challenges in the implementation of fire and gas detection systems include extreme environmental conditions, such as corrosion due to exposure to seawater and high temperatures, and false alarms that reach around 15%. Another obstacle is the lack of technical training for personnel in operating and maintaining the system.